Analysis of Cyanide (CN) in Seagrass as a Bioindicator in Sekotong West Lombok - Alwani Alwani; Agil Al Idrus; M. Yamin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Seagrass is one of the aquatic plants that can be used as a bioindicator in the waters. This research aims to determine the morphological structure of seagrass as bioindicators and the amount of cyanide content in seagrass plants in the waters of Sekotong, West Lombok. This research was conducted in July - August 2021 at Pewaringan Beach, Sekotong, West Lombok. Determination of the sample point is done by purposive sampling. Data were collected using line transect method simple random sampling ÃÂ at three points. Data analysis was carried out on seagrass plants with complete roots, stems, and leaves using a spectrophotometer at BLKPK NTB Province. The results showed that the characteristics of seagrass in the three research locations had a slightly muddy sandy substrate and slightly sandy muddy, an average leaf ÃÂ length of 21.5 cm, an average leaf ÃÂ width of 1.10 cm, an average stem length of 9.4 cm, diameter the average stem is 0.74 cm, the average root length is 7.29 and the average root diameter is 0.25 cm. The ANOVA test showed that the significant value was <0.05, so there was a significant difference in the morphology of the seagrass. The cyanide content in the waters of Pewaringan Beach was found to be on average 12,341 mg/kg or 0.495 mg/L. According to the Ministry of Health of the Republic of Indonesia No. 57 of 2016 the standard cyanide content in waters is 0.5 mg/L. So that the cyanide content in the waters of Pewaringan Beach is still within safe limits.